International entrepreneurship : a comparative analysis - Freeman, Susan, 1958-; Zhu, Ying, 1961-; Warner, Malcolm (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This book explores the importance of entrepreneurs in driving economic growth as the world economy grows and becomes more integrated and more challenging. It examines the situation in both advanced and developing countries and shows how the entrepreneurial orientation of the founders of small and medium sized enterprises has resulted in phenomenal growth, often fuelled by innovation and new technology. It contrasts the experiences of Chinese family business in China and among the overseas Chinese with the experiences of family businesses in the United States and Europe. One important conclusion is that there has been a noticeable fall in entrepreneurial proclivity in the advanced economies, in contrast to the position in emerging economies"--
Introduction: the origins of entrepreneurship and internationalization international entrepreneurship and schools of thought -- International entrepreneurship: its emergence from international business and entrepreneurship -- International entrepreneurship in emerging and Western markets: the rising influence of China -- Ethnicity and entrepreneurship -- Australia and its history of immigration and entrepreneurship -- Internationalization of Chinese entrepreneurship -- Ethnic entrepreneurs in the West vis à vis those in the East: Jewish entrepreneurs' experience -- Conclusion: comparative analysis of internationalization of entrepreneurship.
OCLC-licensed vendor bibliographic record.
Keywords: Entrepreneurship; SOCIAL SCIENCE / Ethnic Studies / Asian American Studies